Fractured Relationships: Exploring Municipal Defiance in Colorado, Texas, and Ohio. (June 2016) - Fisk, Jonathan M.
Municipalities are on fracking's front lines. Unlike the extraction techniques of the past, many of today's operations are located within a mile or two of residential areas. Yet, little scholarly attention has been paid to the factors that can precipitate municipal challenges to the state's authority. For some, the decision to oppose the state may be related to environmental concerns, while in other communities, leaders are much more concerned about how development impacts homeowners. Recognizing this debate, this article examines local defiance in the era of fracking with a sample of Colorado, Texas, and Ohio communities.